2020
DOI: 10.1002/admi.201902170
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Fabrication and Transfer Method of Vertically Aligned Carbon Nanotubes on a Mo/Ni Bilayer for Wearable Energy Devices

Abstract: Carbon nanotubes are a promising material for flexible/wearable electrochemical device due to their mechanical softness, chemical stability, and high conductivity. Furthermore, the vertically aligned form of carbon nanotubes (VACNTs) have a large surface area due to their unique three‐dimensional (3D) nanostructure. Thus, VACNTs are particularly useful for wearable electrochemical sensors and/or energy devices. However, VACNTs are generally grown via a high‐temperature chemical vapor deposition process, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The power supply devices (Figure H), including energy storage, harvest, and transfer devices, need to be miniaturized, lightweight, ultrathin, and stretchable for application to biointegrated electronics. The large specific surface area, excellent energy storage characteristics, and deformability of the nanomaterials are beneficial for energy storage devices for such purposes. Despite tremendous research efforts, ideally soft energy storage devices, which exhibit high stretchability, high energy storage capacity, and long-term stability, are yet to be developed.…”
Section: Device Components For Soft Bio-integrated Electronicsmentioning
confidence: 99%
“…The power supply devices (Figure H), including energy storage, harvest, and transfer devices, need to be miniaturized, lightweight, ultrathin, and stretchable for application to biointegrated electronics. The large specific surface area, excellent energy storage characteristics, and deformability of the nanomaterials are beneficial for energy storage devices for such purposes. Despite tremendous research efforts, ideally soft energy storage devices, which exhibit high stretchability, high energy storage capacity, and long-term stability, are yet to be developed.…”
Section: Device Components For Soft Bio-integrated Electronicsmentioning
confidence: 99%
“…The kirigami-based array design allows transferring the high-density image sensor array from a planar surface to a curvilinear surface while minimizing the mechanical stress. [61][62][63][64][81][82][83][84][85] Furthermore, the ultrathin and soft 2D materials (i.e., MoS 2 and graphene) help in preventing mechanical fractures of the array on a hemispherical surface. The photodetector exhibited high photoabsorption efficiency [40] (>5 × 10 7 m -1 ), photoresponsibility [40] ≈2200 A W -1 ), and fracture strain [40] (≈23%), and the curved image sensor array could be conformally integrated on a hemispherical surface with small induced strains (Figure 3g).…”
Section: Chambered-eye-inspired Artificial Visionmentioning
confidence: 99%
“…A theoretical study of the water-assisted thin film delamination showed that it is feasible to conduct wafer-scale layer transfer with almost 100% yield without any significant performance degradation of the exfoliated devices . In the past decade, a range of devices including amorphous Si thin film solar cells, nanowire electronic devices, resistive random access memory (RRAM) devices, magnetic nanodevices, solar absorbers for solar thermal energy conversion, and supercapacitors have been developed via a water-assisted thin film delamination method. Wie et al showed the integration of various nanomaterials (e.g., silver nanowire, crystalline Si nanomembranes, MoS 2 ) on a Ni/SiO 2 /Si substrate for the development of various functional devices and separation of the fabricated device layer via water-assisted thin film delamination method .…”
Section: Crack-assisted Layer Transfer With Interfacial Fracture Toug...mentioning
confidence: 99%